Construction of spirocycles containing highly substituted pyrroli-dine and 1-indanone motifs with spiro quaternary stereogenic centers via 1, 3-dipolar cycloaddition of 2-alkylidene-1-indanone and azomethine ylides promoted by simple imidazolium salts1. Issue 87 (20th September 2015) - Hu, Wei-Qiang; Cui, Yan-Su; Wu, Zhi-Jun; Zhang, Chuan-Bao; Dou, Pei-Hao; Niu, Song-Yang; Fu, Ji-Ya; Liu, Yong
<x xml:space="preserve">Abstract</x> The 1, 3-dipolar cycloaddition of 2-alkylidene-1-indanone with azomethine ylides has been successfully developed promoted by simple imidazolium salts to construct a variety of spirocycles, containing highly substituted pyrrolidines, in excellent yields (up to 99%).